Citrus Selection Achievement - M. Z., Fakhrutdinov; S.Ya. , Islamov; G.S., Khodjayeva (Researchparks Publishing, 2024)
Worldwide citrus selection has been dealt with by many scientists in different periods, such as Gallezio (1811), Decandol (1824), Engler (1897), Swingle (1943), Luss (1947), Tanaka (1954), Fakhrutdinov (1960) and others: Under the development of citrus fruiting is understood the acquisition of a fertile and high-quality product at as little cost as possible. There are various measures to do this, which include improving productivity and its quality by improving care, organizing specialized smallholding farms, applying in the production of new, fertile, varieties with good crop quality, introducing advanced agrotechnical measures, combating diseases and pests with new advanced methods, caring for lemon, orange, tangerine and grapefruit seedlings, harvesting, storage, export processing works and creating new varieties.